2017
DOI: 10.3389/fnins.2017.00259
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Functional Connectivity Architecture in Participants with Chronic Insomnia Disorder Accompanying Cognitive Dysfunction: A Whole-Brain, Data-Driven Analysis

Abstract: Objectives: Although it is widely observed that chronic insomnia disorder (CID) is associated with cognitive impairment, the neurobiological mechanisms underlying this remain unclear. Prior neuroimaging studies have confirmed that a close correlation exists between functional connectivity and cognitive impairment. Based on this observation, in this study we used resting-state functional magnetic resonance imaging (rs-fMRI) to study the relationship between whole brain functional connectivity and cognitive func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 76 publications
(110 reference statements)
1
31
1
1
Order By: Relevance
“…Moreover, CID patients were required not have taken medicine that would influence brain function two weeks before experiment. The inclusion criteria for CID patients were as follows: ( Spiegelhalder et al, 2015 ) duration of insomnia symptoms, such as fatigue, testiness, or cognitive decline, were required no less than three months; ( Kay and Buysse, 2017 ) PSQI score ≥8; ( Li et al, 2016 ) no neurological or psychiatric disorders, such as stroke, depression (HAMD ≤ 17), and anxiety (HAMA ≤ 14) ( Pang et al, 2017 ) etc. ; ( Altena et al, 2008 ) no other sleep disorders (such as sleep-related movement disorders, hypersomnia, or parasomnia); ( Baglioni et al, 2014 ) right-hand dominance (determined by Chinese Handedness Inventory that suits Chinese people, including 10 test items) and native chinese speakers; ( Wang et al, 2012 ) age 20–60 years; ( Biswal et al, 1995 ) no medication or substance abuse, such as caffeine, nicotine, or alcohol; ( Fox and Raichle, 2007 ) no abnormal signal found by T2-weighted dark-fluid and T1-weighted MR images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CID patients were required not have taken medicine that would influence brain function two weeks before experiment. The inclusion criteria for CID patients were as follows: ( Spiegelhalder et al, 2015 ) duration of insomnia symptoms, such as fatigue, testiness, or cognitive decline, were required no less than three months; ( Kay and Buysse, 2017 ) PSQI score ≥8; ( Li et al, 2016 ) no neurological or psychiatric disorders, such as stroke, depression (HAMD ≤ 17), and anxiety (HAMA ≤ 14) ( Pang et al, 2017 ) etc. ; ( Altena et al, 2008 ) no other sleep disorders (such as sleep-related movement disorders, hypersomnia, or parasomnia); ( Baglioni et al, 2014 ) right-hand dominance (determined by Chinese Handedness Inventory that suits Chinese people, including 10 test items) and native chinese speakers; ( Wang et al, 2012 ) age 20–60 years; ( Biswal et al, 1995 ) no medication or substance abuse, such as caffeine, nicotine, or alcohol; ( Fox and Raichle, 2007 ) no abnormal signal found by T2-weighted dark-fluid and T1-weighted MR images.…”
Section: Methodsmentioning
confidence: 99%
“…Some other studies have found disrupted resting-state FC using seed-based region-to-region FC, such as in the amygdala, insula, posterior cingulate cortex, and hippocampus ( Huang et al, 2012 ; Wang et al, 2017 ). Li and Pang et al divided the brain into 116 regions and identified abnormal FCs by comparing the Pearson's correlation coefficients of each pair, and their results indicated aberrant FCs in widely distributed regions ( Li et al, 2017 ; Pang et al, 2017 ). Many previous findings in fMRI described above were focused on the dysfunctions of the circumscribed brain regions or FC changes between two different brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Modern neuroimaging methods allow for a non-invasive mapping of structural and functional brain networks and provide a promising way to shed light on the neurobiological foundations of insomnia to achieve clinically relevant information that can help target interventions. An increasing number of studies have investigated functional connectivity alterations related to insomnia (Huang et al, 2012;Killgore et al, 2013;Chen et al, 2014;Li et al, 2014;Nie et al, 2015;Zhou et al, 2016;Li et al, 2017;Lu et al, 2017b;Pang et al, 2017;, but as a number of recent reviews point out, the results are relatively inconsistent so far (Spiegelhalder et al, 2015;Kay and Buysse, 2017;Tagliazucchi and van Someren, 2017). This inconsistency may stem from the variety of methods used (Spiegelhalder et al, 2015), but may also be influenced by sleep confounds (Tagliazucchi and Laufs, 2014) and insomnia heterogeneity (Chee, 2013;Benjamins et al, 2017;Kay and Buysse, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies for insomnia have made substantial effort to understand the neuromechanisms of insomnia. Previous studies found aberrant brain metabolism and connectivity related to the prefrontal cortex, insular cortex, amygdala, precuneus and caudate in primary insomnia [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For example, using PET, Nofzinger et al [4] found smaller decrease in relative metabolism from waking to non-REM sleep states in the ascending reticular activating system, hypothalamus, thalamus, insular cortex, amygdala, hippocampus, anterior cingulate and medial prefrontal cortices, which supports the CNS hyperarousal hypothesis.…”
Section: Introductionmentioning
confidence: 74%